Construction of Hierarchical K1.39Mn3O6 Spheres via AlF3 Coating for High‐Performance Potassium‐Ion Batteries - Zhao, Shuoqing; Yan, Kang; Munroe, Paul; Sun, Bing; Wang, Guoxiu (Advanced energy materials, 2019)
Potassium‐ion batteries are attracting great interest for emerging large‐scale energy storage owing to their advantages such as low cost and high operational voltage. However, they are still suffering from poor cycling stability and sluggish thermodynamic kinetics, which inhibits their practical applications. Herein, the synthesis of hierarchical K1.39Mn3O6 microspheres as cathode materials for potassium‐ion batteries is reported. Additionally, an effective AlF3 surface coating strategy is applied to further improve the electrochemical performance of K1.39Mn3O6 microspheres. The as‐synthesized AlF3 coated K1.39Mn3O6 microspheres show a high reversible capacity (about 110 mA h g−1 at 10 mA g−1), excellent rate capability, and cycling stability. Galvanostatic intermittent titration technique results demonstrate that the increased diffusion kinetics of potassium‐ion insertion and extraction during discharge and charge processes benefit from both the hierarchical sphere structure and surface modification. Furthermore, ex situ X‐ray diffraction measurements reveal that the irreversible structure evolution can be significantly mitigated via surface modification. This work sheds light on rational design of high‐performance cathode materials for potassium‐ion batteries. Hierarchical AlF3‐coated K1.39Mn3O6 microspheres with a 3D porous microstructure are synthesized and investigated as cathode materials for potassium‐ion batteries. The hierarchical structure design combined with AlF3 surface coating not only improves the rate capability and cycling stability of K1.39Mn3O6 microspheres but also alleviates their volume expansion during potassium‐ion insertion/extraction.